Association between Tissue miR-141, miR-200c and miR-30b and Bladder Cancer: A Matched Case-Control Study - Mahdavinezhad, Ali; Mousavibahar, Seyed Habibollah; Poorolajal, Jalal; Yadegarazari, Reza; Jafari, Mohammad; Shabab, Nooshin; Saidijam, Massoud (Urology Journal, 2015)
Abstract Purpose: To evaluate the expression of microRNAs in tissue samples from patients with bladder cancer and to compare it with healthy adjacent tissue samples as controls. Materials and Methods: Thirty five tissue samples from patients with newly diagnosed untreated bladder transitional cell carcinoma and 35 adjacent normal urothelium were collected during 2013 to 2014. TRIzol reagent was used to isolate total RNA including microRNAs. RNA concentration and purity were determined using a nanodrop spectrophotometer. Also 1% agarose gel electrophoresis was used to assess integrity of RNA. Real-Time Quantitative Reverse Transcription PCR (qRT-PCR) method was performed using the PARSGENOME microRNA RT-PCR system. Data was analyzed by STATA 11. Results: A couple of patients were female the remainder were male. Mean age of patients were 71.06 ± 11.43 years. The expression level of miR-30b, miR-141 and miR-200c in case group were significantly higher than that of control normal tissue samples. miR-141 had higher expression rate in malignant tissue than two other miRNAs (P < .001). Conclusion: There was a more expression rate of miR-200c, miR-141 and miR-30b in bladder cancer tissues than healthy adjacent control tissues. Further studies are needed to draw final conclusion.